2022
DOI: 10.3389/fpls.2022.829635
|View full text |Cite
|
Sign up to set email alerts
|

Residue Analysis and the Effect of Preharvest Forchlorfenuron (CPPU) Application on On-Tree Quality Maintenance of Ripe Fruit in “Feizixiao” Litchi (Litchi chinensis Sonn.)

Abstract: Litchi is a highly perishable fruit. Ripe litchi fruit loses quality quickly as they hang on tree, giving a very short hanging life and thus harvest period. This study attempted to explore the roles of cytokinin in regulating fruit ripening and senescence of litchi and examine the possibility of applying cytokinin in “on-tree storage” of the fruit. Exogenous cytokinin, forchlorfenuron (CPPU), was applied at 20 mg L−1 7 weeks after full bloom on litchi (Litchi chinensis cv. Feizixiao) fruit clusters. Color para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This suggested that higher m6A modification levels induced by a relatively higher expression of LcMTA_2 and lower expression of LcALKBH10A might be the important factors for the delay of the maturation of the ‘Feizixiao’ variety induced by exogenous CPPU. CPPU is an inhibitor of ABA biosynthesis, and it had been reported that the application of exogenous CPPU had no significant effect on fruit weight, total sugar, and organic acids, but it did repress the coloration conspicuously by suppressing chlorophyll loss and anthocyanin accumulation in the fruit of the ‘Feizixiao’ variety [ 38 ]. ABA was considered as the critical hormone related to anthocyanin accumulation and chlorophyll loss during litchi fruit ripening [ 19 , 24 , 36 , 39 ], and the fruit of the ‘Feizixiao’ variety that appeared in the ‘stay green’ phenomenon (an uneven pigmenting problem) was considered to be mainly caused by the insufficient anthocyanin content induced by the relative low ABA accumulation during fruit coloration, which result in could not cover up the chlorophyll related determining substances of background color [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that higher m6A modification levels induced by a relatively higher expression of LcMTA_2 and lower expression of LcALKBH10A might be the important factors for the delay of the maturation of the ‘Feizixiao’ variety induced by exogenous CPPU. CPPU is an inhibitor of ABA biosynthesis, and it had been reported that the application of exogenous CPPU had no significant effect on fruit weight, total sugar, and organic acids, but it did repress the coloration conspicuously by suppressing chlorophyll loss and anthocyanin accumulation in the fruit of the ‘Feizixiao’ variety [ 38 ]. ABA was considered as the critical hormone related to anthocyanin accumulation and chlorophyll loss during litchi fruit ripening [ 19 , 24 , 36 , 39 ], and the fruit of the ‘Feizixiao’ variety that appeared in the ‘stay green’ phenomenon (an uneven pigmenting problem) was considered to be mainly caused by the insufficient anthocyanin content induced by the relative low ABA accumulation during fruit coloration, which result in could not cover up the chlorophyll related determining substances of background color [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Forchlorfenuron (CPPU) is a synthetic plant growth regulator with strong cytokinin-like activity [ 1 ]. It has become a popular agrochemical to boost size and improve the quality of fruit [ 2 , 3 ]. CPPU has been extensively used due to the growing market demand for high-quality fruits, which poses a potential health risk to consumers exposed to CPPU from food ingestion.…”
Section: Introductionmentioning
confidence: 99%